Legal Certainty In The Implementation Of Regional Regulations In West Sumatra Based On Minangkabau Customary Values - Miasiratni, Miasiratni; Parlindungan S, Gokma Toni (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study evaluates legal certainty in the implementation of Regional Regulations (Perda) in West Sumatra based on Minangkabau customary values. Using a juridical-empirical approach and normative analysis, this research examines how well these regulations can be integrated into the existing legal system without disregarding local customs. The main findings indicate that although Minangkabau-based Perda are legally recognized, there are inconsistencies in their implementation due to differences between positive law and customary law. This leads to challenges in applying the law consistently and fairly. This research contributes to the literature by highlighting the need for more effective harmonization between state law and customary law to enhance legal certainty in culturally rich regions like West Sumatra. The practical implications include the importance of strengthening cooperation between policymakers and customary communities in the legislative and legal implementation processes.